Vietnamese consulting firms for foreign investors : a study of marketing strategies - Nguyen, Thi Minh Hoa (2011)
Along with the economic reform, Vietnam business environment has changed fast. There is a large presence of newly developing businesses that is coming as a result of the gradual opening of its markets to outside investors. Therefore, we have seen a trend of heightened foreign investments to support the growing infrastructure of business in Vietnam. The development has started with the basic needs for business, for example, construction of buildings, infrastructure, and hotels to accommodate the growing tourism industry, anxious to experience all of Vietnam's natural wonders. From these two facets of business and industrial creation in Vietnam, the technology and know-how has come from foreign companies, and foreign consulting firms who have greatly increased and expedited the foreign investment process for many foreign investors and entrepreneurs wanting to do business within Vietnam.